Primase is required for helicase activity and helicase alters the specificity of primase in the enteropathogen Clostridium difficile - van Eijk, Erika; Paschalis, Vasileios; Green, Matthew; Friggen, Annemieke H.; Larson, Marilynn A.; Spriggs, Keith; Briggs, Geoffrey S.; Soultanas, Panos; Smits, Wiep Klaas (Royal Society Publishing, 2016)
DNA replication is an essential and conserved process in all domains of life and may serve as a target for the development of new antimicrobials. However, such developments are hindered by subtle mechanistic differences and limited understanding of DNA replication in pathogenic microorganisms. Clostridium difficile is the main cause of healthcare-associated diarrhoea and its DNA replication machinery is virtually uncharacterized. We identify and characterize the mechanistic details of the putative replicative helicase (CD3657), helicase-loader ATPase (CD3654) and primase (CD1454) of C. difficile, and reconstitute helicase and primase activities in vitro We demonstrate a direct and ATP-dependent interaction between the helicase loader and the helicase. Furthermore, we find that helicase activity is dependent on the presence of primase in vitro The inherent trinucleotide specificity of primase is determined by a single lysine residue and is similar to the primase of the extreme thermophile Aquifex aeolicus. However, the presence of helicase allows more efficient de novo synthesis of RNA primers from non-preferred trinucleotides. Thus, loader-helicase-primase interactions, which crucially mediate helicase loading and activation during DNA replication in all organisms, differ critically in C. difficile from that of the well-studied Gram-positive Bacillus subtilis model.